2020
DOI: 10.17151/rlee.2020.16.2.13
|View full text |Cite
|
Sign up to set email alerts
|

A study of critical thinking in higher education students

Abstract: The study shows a proposal on specific diagnosis of critical thinking skills in higher education students according to literal, inferential and critical reading levels. A literature review on Critical thinking was done to support concepts. This proposal is adapted from the variables of the information obtained. One of the conclusions shows that the career profile is a determining factor in the result and that motivation and interest are outstanding in the reading and writing processes. Teaching students to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…In addition, the result supports that of Morozova et al’s [ 20 ] study, which showed evidence of the connection between critical thinking ability and independent learning; students who learned to think critically boosted their independent learning. Besides, the current result echoes that of Zuluaga et al [ 37 ], who showed that reading and writing techniques increase students’ argumentation capacity; nonetheless, they lack critical thinking abilities. Moreover, Al-Fneikh [ 51 ] unveiled that the critical thinking level is low among Qassim University students.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, the result supports that of Morozova et al’s [ 20 ] study, which showed evidence of the connection between critical thinking ability and independent learning; students who learned to think critically boosted their independent learning. Besides, the current result echoes that of Zuluaga et al [ 37 ], who showed that reading and writing techniques increase students’ argumentation capacity; nonetheless, they lack critical thinking abilities. Moreover, Al-Fneikh [ 51 ] unveiled that the critical thinking level is low among Qassim University students.…”
Section: Discussionsupporting
confidence: 87%
“…According to the findings, critical thinking achievement is more challenging in English as a second language. According to [ 37 ], reading and writing techniques increase student argumentation capacity; nonetheless, they lack critical thinking abilities.…”
Section: Theoretical Frameworkmentioning
confidence: 99%